2022
DOI: 10.3389/fmicb.2022.898505
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fecal microbiota transplantation from yaks on weaning diarrhea, fecal microbiota composition, microbial network structure and functional pathways in Chinese Holstein calves

Abstract: This study was conducted to investigate the effect of fecal microbiota transplantation (FMT) from yaks on weaning diarrhea, fecal microbiota composition, microbial network structure and functional pathways in Chinese Holstein Calves. In this study, 50 calves were randomly divided into five groups of 10 each: NC group (no supplementation), Control group (normal saline), low concentration FMT group (LFMT, 1 × 108 CFU/ml), high concentration FMT group (HMFT, 1 × 109 CFU/ml), and sterilized FMT group (SMFT, steril… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…However, another study examined the effects of FMT from yaks, whereby it has increased the relative abundance of beneficial bacteria, enhanced microbial network complexity, and promoted essential metabolic and cellular processes in weaned calves. Overall, these findings suggest that FMT could be a valuable strategy for preventing weaning diarrhea and other intestinal diseases in ruminants [121].…”
Section: Therapeutic Approaches To Modulate Gut Microbiotamentioning
confidence: 72%
“…However, another study examined the effects of FMT from yaks, whereby it has increased the relative abundance of beneficial bacteria, enhanced microbial network complexity, and promoted essential metabolic and cellular processes in weaned calves. Overall, these findings suggest that FMT could be a valuable strategy for preventing weaning diarrhea and other intestinal diseases in ruminants [121].…”
Section: Therapeutic Approaches To Modulate Gut Microbiotamentioning
confidence: 72%
“…Lactobacillus plays a good role in improving intestinal epithelial barrier function, maintaining mucosal integrity, competing with pathogenic bacterial, and ameliorating intestinal mucosal damage ( Wu et al, 2020 ). Our previous studies have shown that low-concentration fecal microbiota transplantation (LFMT) reduces the diarrhea incidence of weaned calves with Xinjiang yaks as the donor of fecal microbiota transplantation and Chinese Holstein calves as the recipient of fecal microbiota transplantation, and Lactobacillus was enriched in the intestine ( Li et al, 2022 ). To develop more effective probiotics to alleviate weaning diarrhea in calves, we screened Lactobacillus in the feces of weaned calves after LFMT treatment in a previous study, and identified two potential probiotics for alleviating weaning diarrhea in calves, Lactobacillus reuteri L81 and Lactobacillus johnsonii L29.…”
Section: Introductionmentioning
confidence: 99%